Subclinical peritonitis due to perforated sigmoid diverticulitis 14 years after heart-lung transplantation. - Markogiannakis, Haridimos; Konstadoulakis, Manousos; Tzertzemelis, Dimitrios; Antonakis, Pantelis; Gomatos, Ilias; Bramis, Constantinos; Manouras, Andreas (World J Gastroenterol, 2008)
Acute complicated diverticulitis, particularly with colon perforation, is a rare but serious condition in transplant recipients with high morbidity and mortality. Neither acute diverticulitis nor colon perforation has been reported in young heart-lung grafted patients. A case of subclinical peritonitis due to perforated acute sigmoid diverticulitis 14 years after heart-lung transplantation is reported. A 26-year-old woman, who received heart-lung transplantation 14 years ago, presented with vague abdominal pain. Physical examination was normal. Blood tests revealed leukocytosis. Abdominal X-ray showed air-fluid levels while CT demonstrated peritonitis due to perforated sigmoid diverticulitis. Sigmoidectomy and end-colostomy (Hartmann's procedure) were performed. Histopathology confirmed perforated acute sigmoid diverticulitis. The patient was discharged on the 8th postoperative day after an uneventful postoperative course. This is the first report of acute diverticulitis resulting in colon perforation in a young heart-lung transplanted patient. Clinical presentation, even in peritonitis, may be atypical due to the masking effects of immunosuppression. A high index of suspicion, urgent aggressive diagnostic investigation of even vague abdominal symptoms, adjustment of immunosuppression, broad-spectrum antibiotics, and immediate surgical treatment are critical. Moreover, strategies to reduce the risk of this complication should be implemented. Pretransplantation colon screening, prophylactic pretransplantation sigmoid resection in patients with diverticulosis, and elective surgical intervention in patients with nonoperatively treated acute diverticulitis after transplantation deserve consideration and further studies.
Keywords: Adult; Colon, Sigmoid; Diverticulitis, Colonic; Female; Heart-Lung Transplantation; Humans; Intestinal Perforation; Peritonitis; Postoperative Complications